Study of clay materials rich in iron oxides for the desulfurization of biogas - Ulloa-Solano, Fiorella (2022)
Costa Rica could generate 1,000,000 m3 of methane daily from biogas, but its use as energy source requires the application of desulfurization processes, for which the filtering materials are costly and not locally-sourced. The use of natural filtering substrates that are rich in iron oxides, like clay soils (SR) and red rocks (RR), for the removal of H2S from biogas was studied. The performance of the filter materials was tested in an anaerobic biodigestion system installed in a swine farm, with a daily biogas production of 20-30 m3, 70% methane. Six samples were initially analyzed by X-Ray Diffraction (XRD) and X-Ray Fluorescence (XRF) to quantify the iron oxides (Fe2O3) and two RR samples with the highest percentage of Fe2O3 were selected, RR2 with 4.8% w/w and RR3 with 7.2% w/w. The characterization of the filter media, before and after its use as a filter, was carried out using Scanning Electron Microscopy (SEM), X-Ray Energy Dispersion Spectroscopy (EDS), and XRD combined with Rietveld´s method (XRD-Rietveld). The absorption of sulfur was confirmed and a decrease of 4.8% w/w to 1.1% w/w of the Fe2O3 present in the RR was measured in the RR after applying it in the desulfurization process. The RR with a particle size between 2.4- 6.3 mm can remove up to 28% of H2S. The low efficiency of H2S removal suggests the search for other minerals that have higher fraction of iron oxides, to improve the desulfurization efficiency.